2006
DOI: 10.1002/anie.200503858
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Carbenes

Abstract: New carbenes open up new vistas. The P‐heterocyclic carbene 1 was obtained after planarization of the P atoms in the heterocycle with sterically demanding substituents. The cyclohexyl substituent in the cyclic alkylaminocarbene 2 can be locked by proper substitution in the most sterically demanding conformation such that a low‐coordinate metal center, as in complex 3, is stabilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
132
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 457 publications
(137 citation statements)
references
References 84 publications
2
132
0
3
Order By: Relevance
“…[41] In the 13 C NMR spectra, chemical shifts due to the C-2 carbon are observed in the range ca 140.4-145.5 ppm, which is in agreement with reported data for similar benzimidazolium salts. [42][43][44] The signals for alkyl chain (-CH 2 -) are observed at ca 10.00-49.87 ppm. As expected, in the 1 H NMR spectra of the complexes, the signal corresponding to the NCHN proton resonance is absent due to the loss of this acidic proton after reacting with Ag 2 O.…”
mentioning
confidence: 97%
“…[41] In the 13 C NMR spectra, chemical shifts due to the C-2 carbon are observed in the range ca 140.4-145.5 ppm, which is in agreement with reported data for similar benzimidazolium salts. [42][43][44] The signals for alkyl chain (-CH 2 -) are observed at ca 10.00-49.87 ppm. As expected, in the 1 H NMR spectra of the complexes, the signal corresponding to the NCHN proton resonance is absent due to the loss of this acidic proton after reacting with Ag 2 O.…”
mentioning
confidence: 97%
“…During the past two decades, carbene chemistry has undergone a profound revolution. Persistent triplet carbenes have been observed (3), and singlet carbenes have been isolated (4)(5)(6) and even become powerful tools for synthetic chemists (7,8). However, it is generally believed that singlet carbenes can be isolated only if their electron deficiency is reduced by the presence of at least one π-donor heteroatom directly bonded to the carbene center (9).…”
mentioning
confidence: 99%
“…We have shown that six--electron NHCs B (6), isoelectronic with borazenes (7), are highly thermally stable. Even more strikingly, the two--electron cyclopropenylidene C is stable enough to be isolated at room temperature (8), despite the absence of -donor heteroatoms directly bonded to the carbene center, a necessary criterion for previously isolated carbenes (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%